Improvisation and Freedom - Bakan, Joel (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
This essay, dedicated to Ajay Heble, explores how improvisation relates to two current and synergistic threats to democracy and justice: neoliberalism and illiberalism. It also examines embracing relational freedom as a method of working beyond these threats in our society.